Efficiency of the Machining Process of Circular Shapes by Electrical Discharge Technology - Straka, Ľuboslav; Kuchta, Patrik (International Journal of Engineering and Management Sciences, 2023)
Due to its high machining precision, EDM technology is nowadays very important in the production of high-precision parts for various industries. The high precision of the machined surface in combination with the ability to machine circular surfaces brings, in addition to several advantages, some negatives. The most significant negative of this machining technology is the relatively low productivity as well as the overall production efficiency. The latter is affected by many accompanying phenomena. The main accompanying phenomenon that contributes to the decline in the overall economic efficiency of EDM is the microgeometry errors that occur due to the non-homogeneity of the EDM process. Another accompanying negative phenomenon is the geometric accuracy errors of the machined surface, as a consequence of systematic destruction of the wire tool electrode, faulty interpolation in its guidance, and, last but not least, its vibration. These aspects consequently lead to the requirement for multiple applications of additional finishing cuts, which significantly reduces the overall economic efficiency of the machining process. Therefore, the experimental research aimed to search for options that can effectively help to achieve higher productivity but especially the overall economic efficiency of the machining process.